Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image